Effect of Black Soldier Fly (Hermetia illucens) Larvae Feed Supplement on Length-Weight Relationship of Nile Tilapia (Oreochromis niloticus) - Florien Odhiambo; Julius Manyala; Millicent Ndong’A; Elijah Museve; Hillary M. O. Otieno (Innovations in Agriculture)
One of the main challenges in the aquaculture sector is the high cost of fishmeal, which accounts for about 70 percent of production costs. The black soldier fly (BSF) larvae meal could be an alternative because of its high protein and essential fatty acids contents that are important for fish to grow and develop normally.An analysis was carried out to examine the effect of various feeding strategies on the growth and performance of Nile tilapia (Oreochromis niloticus). Five diets with equal nitrogen content were enriched with BSF larvae meal at different proportions (0%, 25%, 50%, 75%, and 100%). The meal with 0% BSF was used as a control. The length and weight of the fish were collected biweekly, while mortality data were collected daily. The study assessed the length and weight relationship of the fish using the parameter 'b'(regression coefficient). From this research, 'b' was found to range from 3.230 to 3.635, indicating isometric growth patterns. The well-being of the experimental fish was also evaluated through the condition factor 'K,' which ranged from 0.907 to 1.002, suggesting that all the fish were in good health. We, therefore, conclude that substituting the conventional fish means with black soldier fly larvae appears to be possible and impacts fish growth normally.